2018
DOI: 10.1186/s12889-018-6286-8
|View full text |Cite
|
Sign up to set email alerts
|

The ‘invisible homeless’ – challenges faced by families bringing up their children in a remote Australian Aboriginal community

Abstract: BackgroundInsufficient and inadequate housing remain serious and enduring problems in remote Aboriginal communities in the Northern Territory (NT) of Australia. Housing is recognised as a key determinant of persisting inequities between Aboriginal and other Australians in health, as well as education and employment outcomes which in turn impact on health. In our qualitative study exploring strengths and challenges related to early childhood in a remote NT community, insufficient housing emerged as the greatest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 17 publications
(36 reference statements)
1
22
0
Order By: Relevance
“…Rossmandi brought up the wider social disadvantage that overcrowding creates for youth: "When there is no space to stay or sleep at home, kids spend time on the streets, fighting and breaking in." Participants' accounts indicate that overcrowding is a prominent predictor of other social issues in Galiwin'ku, including infectious disease risk, violence, conflict, unemployment, and school attendance, which is consistent with the literature [60,61].…”
Section: Overcrowded Housing and Culturally And Climatically Unsuitabsupporting
confidence: 83%
See 1 more Smart Citation
“…Rossmandi brought up the wider social disadvantage that overcrowding creates for youth: "When there is no space to stay or sleep at home, kids spend time on the streets, fighting and breaking in." Participants' accounts indicate that overcrowding is a prominent predictor of other social issues in Galiwin'ku, including infectious disease risk, violence, conflict, unemployment, and school attendance, which is consistent with the literature [60,61].…”
Section: Overcrowded Housing and Culturally And Climatically Unsuitabsupporting
confidence: 83%
“…Recent research has shown that this needs to change [59]. These separations cause severe social and emotional health and wellbeing challenges among children and parents as Indigenous health and wellbeing is dependent upon connections to kin, community, and country [9,60]. Participants shared that, in mission days, technical education facilities in the community provided them with technical skills.…”
Section: Western Technical and Higher Education Lacking In Communitymentioning
confidence: 99%
“…Given the disproportionately poorer cardiometabolic health experienced by Indigenous Australians [33,34], the role of the built environment in such communities should receive further scrutiny. It is well established that the availability [35] and condition [36,37] of housing, along with provision of functioning household amenities [38], impacts Indigenous health. Similarly, the primary determinants of housing condition in rural and remote communities have also been explored in detail [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Reducing the negative effects of household crowding is consistently identified as one of the major health priorities for Aboriginal and Torres Strait Islander people and peak bodies 87,88. The term “household crowding” is considered distinct from “overcrowding” — a term which has been criticised for failure “to recognise the cultural strengths of multigenerational close living” potentially including support, connection, and protective influence of extended family 37,89. However, these benefits accrue when people have sufficient control over the people and the numbers of people who they choose to live with, and when there is adequate housing design and infrastructure to support household size 89.…”
Section: Chapter 4 Critical Elements Of a Comprehensive Approach To Ementioning
confidence: 99%
“…The term “household crowding” is considered distinct from “overcrowding” — a term which has been criticised for failure “to recognise the cultural strengths of multigenerational close living” potentially including support, connection, and protective influence of extended family 37,89. However, these benefits accrue when people have sufficient control over the people and the numbers of people who they choose to live with, and when there is adequate housing design and infrastructure to support household size 89. Household crowding with a negative effect on health is often the result of culturally and climatically inappropriate housing design.…”
Section: Chapter 4 Critical Elements Of a Comprehensive Approach To Ementioning
confidence: 99%